Sosialisasi Pengenalan Olahraga Atletik Kids pada Siswa Sekolah Khusus Olahraga (SKO) RIAU - Nova Risma; I Bagus Endrawan; Raffly Henjilito (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity aimed to enhance students’ understanding of and interest in athletics at the Riau Sports Special School (Sekolah Khusus Olahraga/SKO Riau) through the Athletics for Kids approach. Athletics for Kids is a modified athletics learning model designed according to children’s characteristics, emphasizing play-based activities, safety, and the development of fundamental movement skills. The implementation methods included socialization sessions, demonstrations, hands-on practice, and reflective activities. The participants were SKO Riau students who actively engaged in all stages of the program. The results indicated an improvement in students’ understanding of basic athletics concepts, increased enthusiasm and active participation, and enhanced fundamental movement skills, particularly running, jumping, and throwing. This activity contributes positively to early-age sports development and may serve as an initial model for introducing athletics through the Athletics for Kids approach in sports-oriented school settings.